Bisexual Men’s Experiences with Discrimination, Internalized Binegativity, and Identity Affirmation: Differences by Partner Gender - Sarno, Elissa L. (Arch Sex Behav, 2020)
Bisexual individuals experience unique forms of discrimination related to their sexual orientation (e.g., anti-bisexual prejudice), which occurs from both heterosexual and gay/lesbian individuals. Bisexual individuals may experience stigma differently depending on the gender of their relationship or sexual partners, because they may be perceived as heterosexual if they have a partner of a different gender and as gay/lesbian if they have a partner of the same gender. The present longitudinal study investigated within-persons differences in anti-bisexual experiences, internalized binegativity, and bisexual identity affirmation based on the gender of participants’ serious relationship partners and gender of sex partners in a sample of 180 young bisexual men. Results indicated that young bisexual men experienced more interpersonal hostility from both heterosexual and gay/lesbian individuals when their serious relationship partner was female. No significant differences were found in other types of anti-bisexual prejudice, internalized binegativity, or bisexual identity affirmation by serious partner gender. For sexual partner gender, men who had only male sex partners experienced more sexual orientation instability attitudes from heterosexual and lesbian/gay individuals; men with only female sex partners experienced more sexual irresponsibility attitudes from heterosexuals, but not from lesbian/gay individuals; and, like those with female serious relationship partners, men with only female sex partners had more frequent experiences of interpersonal hostility from heterosexual and lesbian/gay individuals. Results indicate that bisexual men experience unique forms of prejudice based on the gender of their relationship and sexual partners. Implications for the mental health of bisexual men are discussed.